Penerapan Dan Penegakan Hukum Yang Ada Di Lingkungan Pengadilaan Agama Curup Kelas IB - Vicky Fernando; Stevri Ikandar (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The internship program at the Religious Court of Curup Class IB serves as a practical learning process for students of the Faculty of Law, University of Bengkulu, enabling them to apply theoretical knowledge gained during university studies into real institutional work environments. This internship provides direct experience in case administration, court proceedings, public service mechanisms, and the implementation of judicial principles that emphasize simplicity, efficiency, and affordability. Throughout the internship, the student was involved in various activities, including case file management, court documentation, frontline service at the Integrated Service Center (PTSP), and observation of the duties and functions of judicial officers. Although the Religious Court does not adjudicate criminal cases, students specializing in criminal law still benefit academically by examining intersections between family law cases and potential criminal elements, such as domestic violence, family neglect, identity forgery, and sexual violence. This program not only enhances students’ practical understanding of the judicial process but also strengthens essential professional skills, including discipline, integrity, communication, and teamwork. Therefore, the internship plays a significant role in preparing students for future professional legal careers and improving their competencies as prospective law graduates.